The representation of Afro-Peruvian culture in Ricardo Palma’s story «El rey del monte» - Pérez Abanto, Gianfranco Omar (2021)
Following the reflective spirit of our narrator Ricardo Palma and seeing how he shows the multi-ethnic aspect of the society of his time, by giving prominence to mulattos, zambos and blacks, the purpose of this paper is to carry out an analysis of the story «El rey del monte», a text found in the work Tradiciones peruanas, which narrates the formation of the black brotherhoods in the 18th century and the misfortunes suffered by its protagonists. This article also seeks to give visibility to and revalue Afro-Peruvian culture.